Anticancer insights of Phyla nodiflora against Cyclooxygenase-2 through Conformational Molecular Dynamic Simulations (International Journal of Environmental Sciences, 2025)
Cancer is one of the most fatal diseases throughout the world. Different types of approaches are used for the treatment of cancer and one of them is using medicinal plants to reduce side effects. For the treatment of cancer, there are many proteins and cytokines to be targeted like the cyclooxygenase (COX-2) enzyme. High levels of COX-2 enzyme and prostaglandin were found in patients suffering from cancer. This points towards the potential of targeting this enzyme to inhibit its enzymatic activity and thus reduce prostaglandin. Phyla nodiflora has been reported to induce apoptosis and cell cycle progression in MCF-7 breast carcinoma cells showing higher expression of transcription factors inducing tumorigenesis. Increased antioxidant activity in Ehrlich-Lettre ascites carcinoma (EAC-bearing) mice may be responsible for the anticancer effect. We decided to conduct in vitro experimental and Insilico study including antioxidant activity, molecular docking, molecular dynamic simulation, drug-likeness, ADME and toxicity to identify therapeutic agent of Phyla nodiflora to verify anticancer and antioxidant activity of the plant and to verify either these compounds are harmful or safe for human body. The results show that methanol extract of the plant has potential as antioxidant and molecular docking shows that compounds of the plant including 8-methoxyluteolin (-8.8kcal/mol), 8-methoxyapigenin (-8.3kcal/mol) and3-methylherbacetin (-9.1kcal/mol) to be best potential drug candidates as they have highest binding affinity, follow Lipinski guidelines of five as well and the RMSD and RMSF show that they have strong binding interaction with receptor and show stability. In this study we have reported three bioactive molecules 8-methoxyluteolin, 8-methoxyapigenin and 3-methylherbacetin from Phyla nodiflora which may act as drug candidates and therapeutic agents for treatment of cancer while targeting the COX-2 enzyme.